miR-135a Regulates Atrial Fibrillation by Targeting Smad3 - Xueting Fan; Kai Feng; Yonghui Liu; Leixi Yang; Yizhuo Zhao; Liping Tian; Yiqun Tang; Xiaozhi Wang (Cardiovascular Therapeutics)
Background. Atrial fibrillation (AF) is the most common arrhythmia in clinical. Atrial fibrosis is a hallmark feature of atrial structural remodeling in AF, which is regulated by the TGF-β1/Smad3 pathway. Recent studies have implicated that miRNAs are involved in the process of AF. However, the regulatory mechanisms of miRNAs remain largely unknown. This study is aimed at investigating the function and regulatory network of miR-135a in AF. Methods. In vivo, the plasma was collected from patients with AF and non-AF subjects. Adult SD rats were induced by acetylcholine (ACh) (66 μg/ml)-CaCl2 (10 mg/ml) to establish an AF rat model. In vitro, atrial fibroblasts (AFs), isolated from adult SD rats, were treated with high-frequency electrical stimulation (HES) (12 h) and hypoxia (24 h) to mimic the AF and atrial fibrosis, respectively. miR-135a expression was detected through quantitative real-time polymerase chain reaction (qRT-PCR). The association between miR-135a and Smad3 was speculated by the TargetScan database and confirmed by the luciferase reporter assay. Fibrosis-related genes, Smad3, and TRPM7 were all assessed. Results. The expression of miR-135a was markedly decreased in the plasma of AF patients and AF rats, which was consistent with that in HES-treated and hypoxia-treated AFs. Smad3 was identified as a target of miR-135a. the downregulation of miR-135a was associated with the enhancement of Smad3/TRPM7 expressions in AFs. Additionally, the knockdown of Smad3 significantly reduced the expression of TRPM7 and further inhibited atrial fibrosis. Conclusions. Our study demonstrates that miR-135a regulates AF via Smad3/TRPM7, which is a potential therapeutic target for AF.